Integrated Wheat Management for Improved Wheat Yield and Protein in Kansas - B. R. Jaenisch; R. P. Lollato (Kansas Agricultural Experiment Station Research Reports, 2019)
In Kansas, seven to nine million acres of winter wheat are sown annually with grain yields averaging about 40 bu/a. Variety selection and management strategies are critical decisions to maximize wheat yield. Thus, the main objective of this experiment was to evaluate four wheat varieties and their response to six management strategies at three locations in Kansas. These strategies included a farmer practice, enhanced fertility, economical intensification, increased foliar protection, water-limited yield, and increased plant productivity. Locations were pooled based on tillage practice and environment within Kansas; conventional till in central (Hutchinson and Belleville), and no-till in western (Leoti). In the conventional till analysis, enhanced fertility increased grain yield from 63 bu/a in the farmer practice to 72 bu/a and no other management strategy further increased yields. Thus, WB4303, WB4458, and WB-Grainfield produced a similar grain yield of 72 bu/a; however, Zenda yield was less (68 bu/a). The water-limited yield treatment increased protein concentration from 11.7% in the farmer practice to 14.1%. Protein concentration was 13.1% and 13.6% for WB-Grainfield and WB4303, respectively. In the no-till analysis, the farmer practice and increased plant productivity yielded 51 bu/a and the enhanced fertility increased yields to 64 bu/a. Joe yielded 61 bu/a, which was significantly greater than WB4458 and Byrd (~57 bu/a). In the conventional till, farmer practice measured a protein concentration of 11.2%, which was increased to 12.8% and 13.2% by enhanced fertility and increased plant productivity, respectively. The wheat varieties WB-Grainfield, Joe, and Byrd all had a protein concentration of 12.4%, and WB4458 increased protein concentration to 13.3%. The grain yield and protein concentration of different varieties responded to increases in management input intensity depending on tillage practices and environments. Improved agronomic management based on variety-specific characteristics can help increase wheat productivity in Kansas.
Keywords: wheat; intensive management; fungicide; nitrogen; micronutrients; plant population